المسؤولية الجنائية الدولية للفرد عن ارتكاب جريمة الإبادة الجماعية وفقا لمعاهدة 1919 = International criminal responsibility for individual on committing the crrime of genocide according to the 1919 Treaty of Versailles - Miftah, Ali Umar; Muhammad Husni, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study examines the criminal responsibility of the individual when he committed crimes against humanity, including genocide. This study highlights the center of the individual in contemporary international law where the individual traditional away from responsibility. The study relates the discussion on international criminal responsibility in accordance with the Treaty of Versailles, where Article 228 of the Treaty on it (the government recognizes the German right of states allied and cooperating in providing persons accused of committing acts in violation of the laws of and customs of war to be brought before military courts, and it will be signed as provided by law of sanctions on those persons if convicted). One of the objectives of this study was to determine the responsibility of individuals and groups on criminal acts. And then it was followed by historical approach by reference to the past. This study found that intention of the allies is not justice but deliberately use the symbols of justice in order to achieve political goals.